2011
DOI: 10.1159/000324865
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Therapy with Mitomycin and Ifosfamide in Patients with Gemcitabine-Resistant Metastatic Pancreatic Cancer: A Phase II Trial

Abstract: Background: At the time of upfront treatment failure, over half of the patients with advanced pancreatic cancer are candidates for further treatment. Methods: Patients with metastatic gemcitabine-resistant pancreatic cancer were treated with mitomycin 8 mg/m2 on day 1, ifosfamide 2,500 mg/m2 and mesna 3,000 mg/m2 on days 1–3 every 28 days until progressive disease. A positive responder was defined as a patient who was progression free at 6 months from trial enrolment. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Several clinical trials have evaluated the safety and efficacy of second-line chemotherapy after a gemcitabine-based regimen [6,7,8,9,10,11,12]. According to the NCCN Clinical Practice Guidelines in Oncology (version 2.2012) [13], the regimen includes capecitabine, 5-fluorouracil (5-FU)/leucovorin/oxaliplatin [9] and capecitabine/oxaliplatin [10] as options.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have evaluated the safety and efficacy of second-line chemotherapy after a gemcitabine-based regimen [6,7,8,9,10,11,12]. According to the NCCN Clinical Practice Guidelines in Oncology (version 2.2012) [13], the regimen includes capecitabine, 5-fluorouracil (5-FU)/leucovorin/oxaliplatin [9] and capecitabine/oxaliplatin [10] as options.…”
Section: Introductionmentioning
confidence: 99%
“…The median duration of survival of all patients from the start of ifosfamide therapy was only three months (range, one to more than 26 months) [ 16 ]. A more recent study that employed ifosfamide 2.5 g/m 2 and mesna together with mitomycin C was prematurely stopped because of a median survival of only 3.7 months that was accompanied by high levels of Grade 3–4 toxicity [ 40 ]. Taken together, these studies and our two studies suggest that the encapsulated cells improve median survival, but that benefit is achieved by using 1 gm/m 2 /day ifosfamide without the toxicities experienced by patients receiving 2 g/m 2 /day.…”
Section: Results Of Clinical Trialsmentioning
confidence: 99%
“…A phase II study by Cereda et al looking at salvage therapy with mitomycin C and ifosfamide (analog of cyclophosphamide) in gemcitabine-resistant metastatic pancreatic cancer was closed prematurely based on poor clinical outcomes with 71% of patients experiencing chemotherapy interruption due to progressive disease and 80% of patients demonstrating grade >2 toxicity. This study concluded that the mitomycin C and ifosfamide regimen was considered insufficiently active in gemcitabine-resistant metastatic pancreatic cancer (Cereda et al, 2011). …”
Section: Biomarkers and Therapeutic Targetsmentioning
confidence: 99%